Assessing the diagnostic accuracy of unilateral systematic biopsy combined with targeted biopsy - Wu, Qiyou; He, Chunlei; Tu, Xiang; Chen, Bo; Jiang, Jinjiang; Wang, Jinbao; Chen, Zhouhaoran; Liu, Ruoxuan; Huang, Qiaoxue; Tang, Bo; Yao, Jin; Wei, Qiang (Frontiers in Oncology, 2025)
BackgroundTo evaluate unilateral systematic biopsy (SB) combined with targeted biopsy (TB) and assess its diagnostic accuracy in a real-world, single-centre setting.MethodsPatients with ≥1 MRI lesion who underwent both transperineal 12-core and 3-core TB were enrolled in this study. Detection rates for total prostate cancer (PCa) and clinically significant PCa (csPCa) were compared between TB, unilateral SB+TB, and SB+TB. Pathological consistency was assessed using the kappa test, and logistic regression was used to identify potential predictors.ResultsA total of 250 men were enrolled, of which 126 (50.4%) and 103 (41.2%) exhibited total PCa and csPCa, respectively. Compared to SB+TB, ipsilateral SB combined with TB (ips-SB+TB) had a comparable csPCa detection rate (99/250 vs 103/250, p=0.125), while fewer clinically insignificant PCa were detected (17/250 vs 23/250, p=0.031). In addition, ips-SB+TB demonstrated superior sensitivity for csPCa (96.1%) with an AUC of 0.98. The ips-SB+TB had a significantly higher positive core rate than SB+TB (472/2244 vs. 563/3744, p<0.001). Moreover, ips-SB+TB also had a high consistency of Gleason grade compared to SB+TB (Kappa=0.89). In the multi-lesion cohort, ips-SB+TB also had a comparable csPCa detection rate compared to SB+TB (63/128 vs. 67/128, p=0.125).ConclusionsIn conclusion, our study showed that ips-SB+TB was comparable to SB+TB in detecting csPCa. The results of this study provide valuable insight into the potential of ips-SB+TB as an alternative to SB+TB.